MOTIF DAN KEPUASAN JEMAAT HURIA KRISTEN BATAK PROTESTAN (HKBP) DENPASAR DALAM MENONTON FILM TOBA DREAMS PADA ACARA “NONTON BARENG” - Marpaung, Putri Ulpa; Suryawati, I Gusti Alit; Pradipta, Ade Devia (E-Jurnal Medium, 2019)
ABSTRACT This study want to see the motives and satisfaction Huria Kristen Batak Protestan (HKBP) Denpasar’s congregation on watching the film “Toba Dreams” in Nonton Bareng’s event. This study uses descriptive quantitative methods. The media consumption motive as the reference in this study is the motive put forward by Dennis McQuail. This study found that the four motives according to McQuail could be satisfied. This is evidenced by the value of each motive or sought gratification (gs) which is smaller than the value of each satisfaction or gratification obtained. There are two motives that are satisfied beyond the overall average score, based on the results of the questionnaire spread from 4 indicators used to measure, there are 2 indicators that have an average value greater than the overall motive (4.53), namely indicators of motives of self-identity (4 , 63) as well as motives for integration and social interaction (4.78). And there are 2 indicators that have an average value greater than overall satisfaction (4.65) which is an indicator of satisfaction on the motive of self-identity (4.82) as well as satisfaction with the motives for integration and social interaction (4.85).